Loại trừ nhiễu ngoại lai trên các hệ điều khiển nhiều đầu vào nhiều đầu ra có chứa bất định - Phàn, Vũ Ngọc (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper os to gain insight into the problem of disturbance rejection of MIMO systems with model uncentaty. Disturbance rejection is one of three key problem  of the automatic control. After the introduction, in the second section, the disturbance rejection is discussed in cases where the magnitude of manipulating variables are required to be limited. In Section 3, the disturbance rejection of close-loop  configuration is to be investigated. Finally, in Section 4, some  new results on the disturbance rejection of MOMO systems with model uncertainty are presented.